Genética de populações e relações de parentesco em Ciconiiformes (Aves) - Miño, Carolina Isabel (Universidade Federal de São Carlos, 2010)
Population genetic parameters and genetic relatedness estimates were carried out for Roseate Spoonbill (Platalea ajaja), Wood Stork (Mycteria americana) and Great Egret (Ardea alba egretta) reproductive colonies in Amapa, Pantanal and Rio Grande do Sul (RS), Brazil. Microsatellite genotypes were used to investigate kinship patterns between nestlings sampled inside the same nests, using a variety of analytical approaches. Unrelated nestling-pairs were observed in Roseate Spoonbill nests (6.12% of analyzed nests) and in Wood Stork nests (11.34%); half-siblings were present in Roseate Spoonbill nests as well (1.36%). Only full-siblings were detected inside Great Egret nests. Conspecific brood parasitism (CBP) and extra-pair paternity were proposed to account for the presence of unrelated nestmates and half-siblings, respectively, in Roseate Spoonbill and Wood Stork nests. Those results suggest the occurrence of a mating system different than genetic monogamy in natural populations of those waterbirds. Genetic relatedness was also investigated for adults and offspring, as well as for supposed siblings in Roseate Spoonbill families kept in three zoological facilities in the U.S. Paternity and maternity allocation analyses through maximum-likelihood revealed that errors were present in zoo‟s studbooks in relation to the familial records. We also identified mating between related individuals that were not detected previously by zookeepers. Population genetic parameters were also estimated and demographic processes were assessed for Great Egret reproductive colonies in the Pantanal and Rio Grande do Su, Brazil. Bayesian clustering analyses, assignment tests, analysis of molecular variance, F-statistics estimates, allelic frequency distribution and the G-W index revealed that: i) Pantanal reproductive colonies are genetically differentiated from Rio Grande do Sul colonies; ii) an IBD-like pattern alone cannot explain that differentiation; and iii) genetic signal of a reduction of population size was present for two colonies in the Pantanal and one in Rio Grande do Sul. Results were discussed considering a metapopulation dynamic and also considering that populations from both Brazilian regions represent distinct units and deserve to be treated separately when planning and carrying out conservation and management programs that aim to preserve the species‟ genetic diversity.
Keywords: Genética de populações; Ave aquática; Ardea alba; Mycteria americana; Platalea ajaja; Acasalamento de animais; Cabeça seca; Colhereiro; Garça; Parasitismo de ninho intraespecífico; Paternidade extra-par; Ardea alba; Conspecific brood parasitism; Extra-pair paternity; Genetic mating system; Great Egret; Mycteria americana; Platalea ajaja; Roseate Spoonbill; Waterbirds; Wood Stork; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS